Identifikasi Dampak Perubahan Suhu Pada Dataran Tinggi Dieng, Jawa Tengah - Krisna Wijaya, Michael Gary; Destiyani, Ira; Rahayu, Rina (ECOTAS, 2024)
The Dieng Plateau is an area with an abundant diversity of flora and fauna. However, this area can experience temperatures. The objectives of this research are 1) to determine the factors causing drastic temperature changes in the Dieng area, Central Java; 2) to analyze the impact of temperature changes on the environment, ecosystem, and living creatures in Dieng; and 3) to look for solutions to overcome the negative impacts of changes in Dieng. The research method used is a study of literature from several journals which is then summarized, analyzed, and supported by the researcher's arguments. The Dieng area has different temperatures during the day and at night, making it different. This impacts the agricultural, tourism, health, quality, and availability of drinking water sectors. This can be overcome with several strategies, such as using plants resistant to temperature changes, maintaining body health, and good tourism management. Therefore, significant temperature changes have positive and negative impacts on the ecosystem and surrounding communities.